Associations between physical activity levels and socioeconomic and occupational factors among a large workforce population: insights from an employee health cohort study - Parisa Nejati; Lida Nejati; Jamileh Abolghasemi; Seyed Abbas Motevalian (BMC Public Health, 2026)
Abstract Background Physical inactivity is a growing concern among working populations, with implications for health and productivity. Unlike most previous studies, this research draws on large-scale cohort data from Iranian employees to examine the associations with socioeconomic and occupational factors on physical activity, addressing an evidence gap in workforce health inequalities. Methods This cross-sectional analysis used baseline data collected between 2017 and 2020 from the Employee Health Cohort Study of Iran (EHCSIR), a 15-year longitudinal project to identify risk factors of non-communicable diseases. EHCSIR participants are mainly employees affiliated with the Iran University of Medical Sciences and the Ministry of Health and Medical Education. Of the 4,886 EHCSIR participants, 3,997 with complete physical activity and sociodemographic data were included in the analysis. The data included employee age, gender, marital status, economic status (wealth index), education level, job, and workplace, calculated via principal component analysis (PCA). Physical activity level (i.e., mild, moderate, and vigorous) was measured using the short form of the International Physical Activity Questionnaire (IPAQ) in MET-minutes per week. It was also categorized according to the World Health Organization (WHO) guidelines, which recommend at least 150 min of moderate activity, 75 min of vigorous activity, or a total of 600 MET-minutes per week for adults. Accordingly, the employees were classified as physically inactive or adequately / highly active. The data were analyzed using multivariate logistic regression models together with fixed-effects and random-effects models. Results Nearly 64% of employees in Iran did not meet the WHO’s recommendations for physical activity. The mean total physical activity level was 599.2 and 941.8 MET-minutes per week in female and male employees, respectively. The highest percentage of inactive employees was observed in 45-54-year-olds (66.3%), females (67%), married employees (64.7%), Q4 of the wealth index (70.1%), associates (66.2%), office workers (94.8%), and employees working in health centers (67.1%). Physical activity levels varied significantly across age, gender, job type, workplace, and socioeconomic status. Employees in sedentary roles and higher-SES groups were less likely to be physically active, while younger, male, and hospital-based staff showed higher activity levels. Conclusion These findings reveal structural inequalities in workplace physical activity and underscore the need for targeted health promotion strategies. Several factors may contribute to insufficient physical activity among the participants, including low awareness about the benefits of physical activity, lack of workplace exercise facilities, the high cost of attending fitness classes and other related barriers. Interventions tailored to occupational context—such as PA-friendly environments and flexible scheduling—may help reduce inactivity and improve employee well-being.